2023
DOI: 10.1093/g3journal/jkad151
|View full text |Cite
|
Sign up to set email alerts
|

Strain variation in gene expression impact of hyphal cyclin Hgc1 in Candida albicans

Abstract: Formation of hyphae is a key virulence trait of the fungal pathogen Candida albicans. Hypha morphogenesis depends upon the cyclin Hgc1, which acts together with cyclin-dependent protein kinase Cdc28 to phosphorylate effectors that drive polarized growth. Hgc1 has also been implicated in gene regulation through its effects on two transcription factors, Efg1 and Ume6. Here we report RNA-seq analysis of two pairs of hgc1Δ/Δ mutants and their respective wild-type strains, which lie in two different genetic backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Our rationale is that some functionally important gene expression responses may be heterogeneous or transient and thus may fall below a specific fold-change in one strain. This approach previously indicated that the gene expression impact of hgc1 Δ/Δ and efg1 Δ/Δ mutations in these strain backgrounds correlates well ( R 2 of 0.75 and 0.79, respectively), while that of an nrg1 Δ/Δ mutation correlates poorly ( R 2 of 0.38) ( 15 ). Here, we found that the low-iron responses correlated well, with an R 2 of 0.83 for 820 genes (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Our rationale is that some functionally important gene expression responses may be heterogeneous or transient and thus may fall below a specific fold-change in one strain. This approach previously indicated that the gene expression impact of hgc1 Δ/Δ and efg1 Δ/Δ mutations in these strain backgrounds correlates well ( R 2 of 0.75 and 0.79, respectively), while that of an nrg1 Δ/Δ mutation correlates poorly ( R 2 of 0.38) ( 15 ). Here, we found that the low-iron responses correlated well, with an R 2 of 0.83 for 820 genes (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…A limitation of forward genetic screening is the time-consuming nature of preparing a library of defined mutants, which means that mutant collections are generally only made in a single-strain background. Recent work on strain variation in fungi has demonstrated significant differences in phenotypes between the same deletion or mutation in different strain backgrounds ( 30 33 ). As described above for the lncRNA DINOR ( 6 ) , important validation steps can include making the deletion in multiple strain or clade backgrounds to determine the conservation of the phenotype.…”
Section: Mapping Of Hitsmentioning
confidence: 99%